Strategi Pemasaran Serta Peningkatan Kuantitas Dan Kualitas Produksi Besek Ikan Di Desa Kasiyan Timur Kecamatan Puger Jember - Sauqi, Ahmad; Hidayah, Tamriatin; Sulaksono, Hary; Supeni, Nely (Institut Teknologi dan Sains Mandala, 2024)
Kasiyan Timur Village, Puger District, is one of the villages that is very close to the center of the fish auction. In Kasiyan Timur Village, there is a group of housewives who make besek fish who share their problems with us. Their four problems. 1. The number of production results that do not meet expectations, in quantity cannot meet the daily target 2. Product quality is fragile and not precise. 3. Stagnant from scientific development, especially from the production side. 4. Want broader marketing reach. The solution we provide for this problem is in the form of training in marketing management and production management with the following main topics: increasing productivity with modern production tools towards production quantities that meet expectations. Utilization of modern production tools to produce quality products. Utilizing technology to increase knowledge towards intelligent human resources. Personal selling by implementing pick-up balls and utilizing social media as a marketing tool. Results of community service activities: 1. Able to read marketing opportunities via Facebook and Instagram. 2. Be more open with various knowledge in producing a product, the point is that they are currently very much utilizing YouTube and Google and social media in order to gain knowledge to facilitate their business, especially the science of producing. Already know and have bought a bamboo splitter at Tokopedia. It has been able to increase the quantity of production and maintain its quality, of course, because it has implemented production tools that are quite modern and make it very easy